ENERGY BALANCE ANALYSIS; CASE STUDY OF RURAL ELECTRIFICATION AGENCY (REA) PROJECT IN UNIVERSITY OF MAIDUGURI (FUDMA JOURNAL OF SCIENCES, 2023)
University of Maiduguri has been faced with power supply challenges due to insurgency that negatively affects the north eastern part of Nigeria. Being a research institution, increases in the costs of power and instability of on-grid power supply have jetlagged almost comatose research and academic activates. Government through the Rural Electrification Agency (REA) has provided the University with solar powered streetlights to curb energy consumption and to improve security. This study performed comparative energy cost analysis between solar photovoltaics streetlights executed by REA and public powered streetlights to evaluate energy costs. The objective of this study is to analyse the cost benefits of using solar photovoltaics streetlights, against public powered streetlight. The analyses showed 58% savings in energy costs as against 7.99% rise for public powered streetlights in 2019. The usage of solar photovoltaic streetlights has saved the University of Maiduguri close to 14.8 million Naira from year 2017 to 2019 using 134 solar streetlights poles with 77.22% fil factor.
Keywords: Energy Balance; solar photovoltaic streetlight; public powered streetlight